Bengkalis Regency Halal Tourism Potential in Increasing Regional Income - Hasan, Zulfikar; Azlina, Nur (Universitas Pendidikan Indonesia, 2022)
A b s t r a c tThe research we did was to see how the tourism potential in Bengkalis Regency, where tourism here can also be developed as halal tourism, can impact Bengkalis Regency's regional income. From this, we can observe that the development of halal tourism in the Bengkalis Regency is still not optimal, apart from the lack of a natural position that cannot be used as a tourist spot. This proves that good and integrated management is indispensable for tourism development, especially halal tourism. In this study, we used the descriptive analysis method in addition to looking at the SWOT analysis. We hope that in the future, as researchers, we hope that the Bengkalis Regency government can manage tourist attractions as well as possible and allocate more funds for the development of tourism attractions in the Bengkalis Regency. In addition to increasing Human Resources, especially in mastering English, it is also necessary to promote to the outside world that Bengkalis have a tourist attraction with halal tourism packaging.A b s t r a kPenelitian yang kami lakukan untuk melihat bagaimana potensi pariwisata di Kabupaten Bengkalis, dimana pariwisata disini juga dapat dikembangkan sebagai wisata halal yang dapat berdampak pada pendapatan daerah Kabupaten Bengkalis. Dari sini dapat kita lihat bahwa pengembangan wisata halal di Kabupaten Bengkalis masih belum optimal, karena letak alamnya yang belum bisa dijadikan sebagai tempat wisata. Hal ini membuktikan bahwa pengelolaan yang baik dan terpadu sangat diperlukan untuk pengembangan pariwisata, khususnya wisata halal. Dalam penelitian ini, kami menggunakan metode analisis deskriptif selain melihat analisis SWOT. Besar harapan kami kedepannya sebagai peneliti, kami berharap pemerintah Kabupaten Bengkalis dapat mengelola tempat wisata dengan sebaik-baiknya dan mengalokasikan dana yang lebih besar untuk pengembangan objek wisata yang ada di Kabupaten Bengkalis. Selain peningkatan Sumber Daya Manusia khususnya dalam penguasaan Bahasa Inggris, juga perlu dilakukan promosi ke dunia luar bahwa Bengkalis memiliki daya tarik wisata dengan kemasan wisata halal.